2016
DOI: 10.1093/neuonc/now174
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glioblastoma tumorspheres by combined treatment with 2-deoxyglucose and metformin

Abstract: Background. Deprivation of tumor bioenergetics by inhibition of multiple energy pathways has been suggested as an effective therapeutic approach for various human tumors. However, this idea has not been evaluated in glioblastoma (GBM). We hypothesized that dual inhibition of glycolysis and oxidative phosphorylation could effectively suppress GBM tumorspheres (TS). Methods. Effects of 2-deoxyglucose (2DG) and metformin, alone and in combination, on GBM-TS were evaluated. Viability, cellular energy metabolism st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…Dual inhibition of OXPHOS and glycolysis is able to effectively disrupt energy metabolism and has proven to be effective against tumour growth in multiple preclinical cancer models ( Table 1 ). For example, dual inhibition of glycolysis with 2-DG and OXPHOS with metformin-inhibited tumour growth preclinically in a broad spectrum of tumour models, including breast cancer, prostate cancer, GBM, and sarcoma [ 223 , 224 , 225 , 226 , 227 , 228 , 229 ]. Similarly, HK2 depletion in HCC sensitises cells to metformin [ 230 ].…”
Section: Targeting Metabolic Flexibility As a Mechanism Of Resistamentioning
confidence: 99%
“…Dual inhibition of OXPHOS and glycolysis is able to effectively disrupt energy metabolism and has proven to be effective against tumour growth in multiple preclinical cancer models ( Table 1 ). For example, dual inhibition of glycolysis with 2-DG and OXPHOS with metformin-inhibited tumour growth preclinically in a broad spectrum of tumour models, including breast cancer, prostate cancer, GBM, and sarcoma [ 223 , 224 , 225 , 226 , 227 , 228 , 229 ]. Similarly, HK2 depletion in HCC sensitises cells to metformin [ 230 ].…”
Section: Targeting Metabolic Flexibility As a Mechanism Of Resistamentioning
confidence: 99%
“…They showed that the simultaneous administration of both drugs was associated with the stronger inhibition of tumor cell growth compared to the control. The effect on energy metabolism has been confirmed by measuring ATP levels [197]. Interestingly, the use of only metformin was associated with a weak response in the form of inhibition of GBM-TS proliferation in both its low (5 mM) and high (15 mM) concentration.…”
Section: Potentiating Metformin's Anti-tumor Effectsmentioning
confidence: 83%
“…This allows the drug concentration in cerebrospinal fluid and portal vein to reach 40 µM, while the concentration in the brain tissue reaches 10 µM [4,65,195,196]. While some observations indicate that doses of 50-100 µM are sufficient to inhibit respiration at the cellular level in hepatocytes, in the case of low drug levels, the anti-tumor effect is often not particularly pronounced [14,54,90,197]. In most studies reporting the anti-tumor effects of metformin, the doses used were higher than in the standard antidiabetic treatment [8,35,39,51,52,54,55,198].…”
Section: Potentiating Metformin's Anti-tumor Effectsmentioning
confidence: 99%
“…Vorinostat is a linear hydroxamic acid that inhibits HDAC classes I/II, causing the deacetylation of histones H2A, H2B, H3, and H4 and nonhistone proteins. [61][62][63] Deacetylation of these proteins alters chromatin structure, ultimately altering the transcription activity of target genes. Vorinostat also increases the acetylation state of certain proteins, including p53 and hsp90.…”
Section: Discussionmentioning
confidence: 99%